Nonlinear interaction of charged particles with nonplane counterpropagating laser pulses of relativistic intensities - H. K. Avetissian; Kh. V. Sedrakian (Physical Review Special Topics. Accelerators and Beams, 2010)
The nonlinear threshold phenomena of particle reflection and capture of electrons in the induced Compton process that have previously been revealed in the case of plane monochromatic counterpropagating waves, take place also with the actual nonplane laser pulses of ultrashort duration and lead to particle acceleration. In contrast to analogous phenomena in the induced Cherenkov and undulator processes, the Compton reflection-capture mechanism with laser pulses of relativistic intensities practically may be realized for arbitrary initial energies of particles. The acceleration effect for particles initially in rest is explored numerically, taking into account the significance of this case connected with the relativistic electron bunches of high densities, which currently may be realized by relativistic lasers on the ultrathin solid foils where the electrons initially are almost in rest.